2018
DOI: 10.1029/2017jd028139
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Air‐Sea Environmental Conditions and Interfacial Processes on Extremely Intense Typhoon Haiyan (2013)

Abstract: Typhoon Haiyan (2013) intensified rapidly and reached a central pressure of 895 hPa over the warm northwestern Pacific. To clarify why Haiyan became such an extraordinarily intense tropical cyclone (TC), we investigated the impacts of atmospheric and oceanic conditions and air‐sea interfacial processes on Haiyan's intensity. We performed ensemble experiments with many different initial oceanic conditions and a 7‐km‐mesh atmosphere‐wave‐ocean coupled model. We also performed sensitivity experiments to examine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 90 publications
4
19
0
Order By: Relevance
“…Previous studies found that the intensity forecast of Typhoon Haiyan related with the atmospheric environment, ocean support and other technical details such as horizontal grid resolution and physical parameterization schemes (Lin et al 2014;Islam et al 2015;Wada et al 2018). To understand the factors in atmospheric initial conditions that can improve the intensity forecast, ensemble sensitivity analysis is performed here for Typhoon Haiyan.…”
Section: Case Overviewmentioning
confidence: 99%
“…Previous studies found that the intensity forecast of Typhoon Haiyan related with the atmospheric environment, ocean support and other technical details such as horizontal grid resolution and physical parameterization schemes (Lin et al 2014;Islam et al 2015;Wada et al 2018). To understand the factors in atmospheric initial conditions that can improve the intensity forecast, ensemble sensitivity analysis is performed here for Typhoon Haiyan.…”
Section: Case Overviewmentioning
confidence: 99%
“…More recently, Garg et al (2018) integrated spray-mediated flux formulations from the Andreas corpus along with surface-wave effects into WRF, and found that the spray and surface wave modules produced a stronger hurricane compared to a control simulation. Wada et al (2018) showed that the choice of sea spray parameterization can significantly impact the air-sea latent heat flux in TC simulations. These findings support the conclusion that microscale processes can significantly influence largescale dynamics, and demonstrate how improvements in sea spray flux parameterizations can be used to improve TC simulations.…”
Section: Discussionmentioning
confidence: 99%
“…Gronholz et al (2017) showed improved SST prediction for the North Sea via the use of a higherresolution regional atmospheric forcing rather than a globalscale analysis, and subsequent further improvement by coupling between the atmosphere and ocean. The influence of improved wind forcing by wave-atmosphere coupling was demonstrated by Wahle et al (2017) for a similar domain.…”
Section: Introductionmentioning
confidence: 86%